Koordinasi Pengawasan Badan Permusyawaratan Nagari dengan Wali Nagari dalam Penyelenggaraan Pemerintahan Nagari Muara Sakai - Nur Afifah Agusma Yeni; Hasbullah Malau (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
Nagari Government is the administration of government affairs carried out by the Nagari Government and the Nagari Consultative Body (BAMUS). Wali Nagari is the administrator of the government, while BAMUS is the supervisory agency. In carrying out the supervisory function, BAMUS and Wali Nagari need to coordinate so that BAMUS supervision runs well. The phenomenon of the problems that occur is that there are several things related to the administration of Nagari government that are not known by BAMUS. As a result, BAMUS' supervision of Wali Nagari is not comprehensive. The research method used in this research is descriptive qualitative, describing phenomena according to what is happening in the field. This research was conducted in Nagari Muara Sakai, Pancung Problem District, Pesisir Selatan Regency, West Sumatra Province. The result of the research is that the coordination of supervision between BAMUS and Wali Nagari Muara Sakai is carried out through village deliberations, coordination meetings, verbal communication, BAMUS goes directly to the field, and accountability reports. The coordination in the supervision of BAMUS with the Wali Nagari Muara Sakai has not gone well enough. This is because there are several factors that hinder the coordination of BAMUS supervision with Wali Nagari Muara Sakai, namely poor communication between BAMUS and Wali Nagari, unsynchronized actions between BAMUS and Wali Nagari in several activities, lack of ideas for BAMUS Nagari in carrying out supervisory functions, and the lack of transparency of the Wali Nagari regarding some Nagari activities.